The Use of English Songs to Improve Students Listening Skill at SMP Negeri 242 Jakarta - Fatimatuzzahro, Siti; Rodiyah, Siti; Rakhmawati, Ditta Mustika; Wahdini, Lili; Susandi, Deny Gunawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This Classroom Action Research (CAR) study investigates the efficacy of utilizing song media as an instructional tool to enhance students’ listening abilities in English language teaching. The research was conducted in a VIII-C class at SMPN 242 Jakarta, involving 36 students. Employing a quantitative approach, pre-test and post-test cycles were conducted using questionnaire tests, song listening tests with multiple-choice questions, and essays to evaluate changes in students’ perspectives and listening skills. The study revealed that, initially, only 40% of students enjoyed English classes, but after the integration of song media, this percentage increased to 70%. The pre-test scores indicated that 60% of students achieved a "good-very good" rating, which improved in the post-test. The findings suggest a positive impact on students’ listening skills and an increased enjoyment of English sessions through the incorporation of song media. This study contributes valuable insights into the dynamic and engaging potential of songs as instructional tools in language education, fostering a positive learning environment and improving overall language proficiency.